Nickel and cobalt release from earrings and piercing jewellery - analytical results of a German survey in 2014 - Uter, Wolfgang; Wolter, Joerg (Contact Dermatitis, 2018)
BACKGROUND: Nickel and cobalt are important metal allergens, and more knowledge on the levels of exposure to these from everyday contacts is needed. OBJECTIVES: To report the results of a repeat routine surveillance scheme in the Federal Republic of Germany on the release of nickel and cobalt. METHODS: Fifteen laboratories assessed earrings and piercing jewellery items from 12 of the states in 2014, complying with EN 1811:2011 + AC:2012 and using atomic absorption spectrometry, inductively coupled plasma mass spectrometry and inductively coupled plasma optical emission spectrometry for quantification. Kaplan-Meier analysis for left-censored data was employed to account for measurements below the limit of quantification. RESULTS: Nickel release exceeded 0.35 µg/cm2 per week in 26 of 160 piercing posts (16.2%), and 0.88 µg/cm2 per week in 2.0-5.9% of other parts, that is, the current respective 'pass' thresholds, with no change from the previous 2008 survey. The level of cobalt release was lower than that of nickel release, and also significantly lower than in the previous survey. CONCLUSIONS: The finding of the highest level of nickel release from piercing posts, with their deliberately lower threshold of acceptability, is worrying, as is the largely unchanged overall level of nickel release. A regulation on cobalt release is currently lacking; risk assessment and management based on dose-elicitation data are needed.
EVALuna2:35676